2018
DOI: 10.1681/asn.2017050559
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Venous Remodeling and Nonmaturation of Arteriovenous Fistulas

Abstract: The frequency of primary failure in arteriovenous fistulas (AVFs) remains unacceptably high. This lack of improvement is due in part to a poor understanding of the pathobiology underlying AVF nonmaturation. This observational study quantified the progression of three vascular features, medial fibrosis, intimal hyperplasia (IH), and collagen fiber organization, during early AVF remodeling and evaluated the associations thereof with AVF nonmaturation. We obtained venous samples from patients undergoing two-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 22 publications
4
87
0
Order By: Relevance
“…Fibrogenic vein and artery limit AVF outward expansion and induces inward remodeling. A recent report showed that collagen deposition in the vein is associated with AVF failure in patients with ESRD (25). Second, activation of PDGFRA in GMCs induces GMC differentiation into myofibroblasts or VSMCs, directly contributing to CKD-induced neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrogenic vein and artery limit AVF outward expansion and induces inward remodeling. A recent report showed that collagen deposition in the vein is associated with AVF failure in patients with ESRD (25). Second, activation of PDGFRA in GMCs induces GMC differentiation into myofibroblasts or VSMCs, directly contributing to CKD-induced neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, more than 70% of pre-access veins in ESRD patients have significant hyperplasia at the time of surgery [15]. However, recent studies demonstrated that the contribution of pre-existing IH to AVF nonmaturation is likely very limited, as shown by Martinez et al [4] and also by the Hemodialysis Fistula Maturation (HFM) Group [16], which is the largest multicenter prospective study of AVF with standardized training for data collection and ultrasound measurements and uniform criteria for defining stenosis. As for post-operative hyperplasia, its role in AVF non-maturation and failure has been less studied.…”
Section: Vascular Access Maturation and Failurementioning
confidence: 95%
“…As for post-operative hyperplasia, its role in AVF non-maturation and failure has been less studied. However, more and more evidence suggests that the effects of IH on AVF non-maturation seem to have been overestimated [4,17,18]. To date, it remains uncertain and controversial if post-operative IH is a causative factor for AVF failure and if post-operative intimal hyperplasia is a primary cause or simply a worsening factor for AVF failure.…”
Section: Vascular Access Maturation and Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The findings of these studies suggested that neointimal hyperplasia itself does not directly contribute to AVF failure. On the other hand, Vazquez-Padron's group showed that inflammation of vascular smooth muscle cells and increased postoperative medial fibrosis are the main mechanism of poor AVF outward remodeling, which in turn leads to AVF stenosis and failure 28,29 . Based on the result of these studies, thrombosis is more likely a result of AVF stenosis rather than the inciting event of AVF failure.…”
Section: Discussionmentioning
confidence: 99%